Brachytherapy and osteoradionecrosis in patients with base of tongue cancer. (3rd January 2023) - Danielsson, Daniel; Hagel, Eva; Dybeck-Udd, Sebastian; Sjöström, Mats; Kjeller, Göran; Bengtsson, Martin; Abtahi, Jahan; von Beckerath, Mathias; Thor, Andreas; Halle, Martin; Friesland, Signe; Mercke, Claes; et al.
Abstract: Background: Base of tongue cancer incidence and patient survival is increasing why treatment sequelae becomes exceedingly important. Osteoradionecrosis (ORN) is a late adverse effect of radiotherapy and brachytherapy (BT) could be a risk factor. Brachytherapy is used in three out of six health care regions in Sweden. Aims: Investigate if patients treated in regions using BT show an increased risk for ORN and whether brachytherapy has any impact on overall survival. Material and Methods: We used data from the Swedish Head and Neck Cancer Register between 2008–2014. Due to the nonrandomized nature of the study and possible selection bias we compared the risk for ORN in brachy vs non-brachy regions. Results: Fifty out of 505 patients (9.9%) developed ORN; eight of these were treated in nonbrachy regions (16%), while 42 (84%) were treated in brachy regions. Neither age, sex, TNM-classification/stage, p16, smoking, neck dissection, or chemotherapy differed between ORN and no-ORN patients. The risk for ORN was significantly higher for patients treated in brachy regions compared to non-brachy regions (HR = 2, 63, p  = .012), whereas overall survival did not differ (HR = 0.95, p  = .782). Conclusions and Significance: Brachytherapy ought to be used cautiously for selected patients or within prospective randomized studies.